Teaching and testing second language pragmatics and interaction a practical guide - Roever, Carsten (Routledge, an imprint of Taylor & Francis Group, 2022)
"Pragmatic ability is crucial for second language learners to communicate appropriately and effectively; however, pragmatics is underemphasized in language classrooms. This book remedies that situation by connecting theory, empirical research, and practical curricular suggestions on pragmatics for learners of different proficiency levels: It surveys the field comprehensively and, with useful tasks and activities, offers rich guidance for teaching and testing L2 pragmatics. Mainly referring to pragmatics of English and with relevant examples from multiple languages, it is an invaluable resource for practicing teachers, graduate students, and researchers in language pedagogy and assessment."--Provided by publisher.